Spoken Corpus of Radiotelephony Phraseology - Pavlinovic, Mira (Array, 2013)
Voice communication is one of the vital parts of air traffic control. It is “the eyes and the ears” of every pilot. It helps pilots and air traffic controllers operate the plane and maintain safe and expeditious flight. Throughout the years, investigations of many accidents and incidents have found that lack of radiotelephony knowledge and discipline by pilots and controllers has been a major causal factor. According to research, on average one miscommunication happens every hour per radio frequency. This paper gives an outline of a radiotelephony communication spoken corpus that was compiled and will be used as a basis for designing a language technology system that should spot deviations from the prescribed usage of radiotelephony communication. In order to build a corpus there are a number of factors which need to be taken into consideration. These include size, content, representativeness and usability and are discussed in this paper.